Prognostic Value of Rapid Shallow Breathing Index for Weaning Success in Intensive Care Unit Patients under Mechanical Ventilation - Islam, Md Sirajul; Haider, Md Ali; Mallick, Uzzwal Kumar; Mohammad Asaduzzaman, -; Uddin, Md Gias; Raka, Kazi Eshika; Mamtaz, Farhana; Ahmed, Syed Iftekhar; A Elahi, Dewan Mohammad Kudrat; Samad, Khurshida; et al. (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: The weaning success in intensive care unit patients under mechanical ventilation is very important. Objective: The purpose of this study was to investigate the efficacy and effects of rapid shallow breathing index (RSBI) in predicting weaning success in patients with prolonged mechanical ventilation more than 48 hours. Methodology: This prospective cohort study was conducted in the Department of Anesthesia, Pain Palliative & Intensive Care Unit of Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2014 to December 2015 for a period of two (02) years. Patients on mechanical ventilation more than 48 hours with the age of 18 to 60 years were included in this study. During the weaning process, the arterial blood gases (ABG) values was checked and the patients was separated from mechanical ventilation. After measuring RSBI, patients was separated from mechanical ventilator and given T-piece trial (1 to 4 hours) and finally extubated as per advice of ICU consultant and observed for 48 hours. The patients were divided in two groups low RSBI ≤105 breath/min/L and high RSBI >105 breath/min/L. These patients were prospectively followed up to 48 hours in ICU and HDU. Result: A total of 117 patients were included in this study. The validity of RSBI evaluation for trail failure was correlated by calculating sensitivity, specificity, accuracy, positive and negative predictive values. The sensitivity of RSBI was 54.5% (95% CI 23.38% to 83.25%) and specificity was 82.1% (95% CI 73.43% to 88.85%). However, positive predictive value and negative predictive value were 24.0% (95% CI 13.84% to 38.30%) and 94.6% (95% CI 90.05% to 97.10%) respectively. The accuracy was found 79.5% (95% CI 71.03% to 86.39%). Receiver-operator characteristic (ROC) were constructed using RSBI of the weaning outcome, which gave a RSBI cut off value of ≥88 as the value with a best combination of sensitivity (72.7%) and specificity (61.3%), accuracy (60.7%), positive predictive value (15.7%), negative predictive value (95.5%) for trail failure. Conclusion: In conclusion the efficacy and effects of rapid shallow breathing index is found low sensitivity with high specificity in predicting weaning success in patients with prolonged mechanical ventilation more than 48 hours. Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 9-14